Plant litter regulates the effect of nitrogen and water enrichment on ecosystem carbon sequestration in a semi-arid grassland - Chen, Wanjie; Zhao, Xuezhen; Su, Jishuai; Lu, Xiaoming; Bai, Yongfei (Agriculture, ecosystems & environment, 2024)
Plant litter and global change (e.g., nitrogen deposition, increased precipitation) are broadly recognized as key factors regulating terrestrial carbon sinks, especially in arid and semiarid regions. However, significant uncertainties exist regarding how plant litter interacts with nitrogen (N) deposition and/or increased precipitation to affect ecosystem carbon dynamics. Based on a three-year experiment combining litter manipulation with water and nitrogen addition in a semi-arid grassland, we examined how plant litter regulated ecosystem carbon flux responses to N or water addition by altering soil environment, plant composition, and soil microbial community properties. We found that water and N addition independently increased net ecosystem productivity (NEP) by 21 % and 20 %, respectively. However, these effects were dependent upon plant litter dynamics and the amount of growing season precipitation. Compared to litter ambient, litter removal enhanced the beneficial effect of N addition on NEP due to increases in aboveground net primary productivity and the cover of forbs. Litter addition strengthened the positive effects of water addition on NEP, largely through increasing soil moisture and the cover of perennial rhizomatous grass. The positive effect of N addition on NEP increased with growing season precipitation, whereas the effect of water addition on NEP decreased with increasing growing season precipitation. These findings underscore the urgency of incorporating plant litter dynamics into the terrestrial carbon cycle models, as they can significantly amplify the ecosystem-level carbon sink response to specific global change drivers. •Water and N addition boosted carbon uptake more than carbon emission.•Litter removal enhanced the positive effect of N addition on net ecosystem productivity (NEP).•Litter addition strengthened the positive effects of water addition on NEP.•Plant litter can amplify carbon sink response to specific global change drivers.